Differential Relations Between Parenting and Emotion Regulation in Children with ASD Across Dyadic and Independent Contexts. - Baker, Jason K.; Fenning, Rachel M.; McElvain, Perri (Journal of Autism & Developmental Disorders, 2026)
Many children with ASD exhibit difficulties with emotion regulation that greatly impair functioning. Certain intrinsic correlates of dysregulation have been identified in this population, but the search for potential environmental influences has been less fruitful. The current study examined several aspects of parenting as correlates of observed regulation in Autistic children, as measured in both parent-child and independent regulatory contexts. A diverse sample of 76 children with ASD aged 6 to 10 years participated in frustrating laboratory tasks with and without their primary caregivers, and the caregivers completed a parenting questionnaire. Emotion regulation, parental scaffolding, and gentle guidance were coded from videotaped interaction, and scores of parental involvement, positive parenting, and inconsistent discipline were obtained through parent report. Differential relations were observed between parenting and children's regulation when considered across contexts, with parental scaffolding associated with children's dyadic regulation and parents' reports of their involvement and discipline associated with children's independent regulation. Findings support previous evidence identifying a potential delay in the internalization of parental co-regulatory support in Autistic children, and highlight parental involvement as a previously unidentified unique correlate of independent regulation in this population. Implications for conceptualizations of emotion regulation in autism are discussed as is the importance of extending findings through further longitudinal research.